"Fighting corruption" or "fighting the corrupt elite"? Politicizing corruption within and beyond the populist divide. Issue 4 (18th May 2020) - Engler, Sarah
ABSTRACT: Corruption has become a central issue of electoral campaigns in Central and Eastern Europe. The EU and international economic organizations first emphasized the fight against corruption as an important indicator of good governance. The topic of corruption, however, has also gained momentum on different terms. Populists praise "the good people" and demonize the " corrupt elite". As a result, anti-corruption claims are often only seen as a substitute of anti-elite rhetoric within the populist discourse. This article sheds light on the way the term "corruption" is used in electoral campaigns and argues that we do not get the full picture of the anti-corruption discourse, if we only focus on the populist narrative. Particularly, it argues that the "good governance"-framework creates incentives for pro-European and pro-market parties to politicize corruption independently of anti-establishment claims. Statistical analyses based on a new expert survey covering the campaigns of 62 parties in six CEE countries between 2000 and 2016 confirm this claim. While populists along the ideological spectrum use anti-corruption claims to highlight the dishonesty of the political elite, we also find parties that embed the fight against corruption in their pro-European and pro-market campaigns. Moreover, we find that these patterns are stable over time.